Les personnages marginalisés dans les romans d’Ananda Devi - Wiśniewska, Katarzyna (Romanica Silesiana)
Ananda Devi’s family island, Mauritius, constitutes the background for her novels. Mauritius is a multiethnic society whose population is approximate to that of Warsaw, with four main religions and seventeen or eighteen languages (depending on a source), of which eight are used every day. However, this socio-cultural variety which we can find practically everywhere (in common life, beliefs as well as in literature), still remains taboo. The problem of social exclusion is one of the main threads in Devi’s novels. She describes people whose beliefs, convictions, behaviours and external appearance differ from what is commonly accepted by the society. She gives a voice to socially excluded individuals, giving them a chance to speak for themselves. The author concentrates on marginalization and rejection of women who are “different” due to appearance, deformation of the body, or bad karma. Key words: Ananda Devi, Mauritius, social exclusion, women.